One-Year Clinical Outcomes With SAPIEN 3 Transcatheter Aortic Valve Replacement in High-Risk and Inoperable Patients With Severe Aortic Stenosis. Issue 2 (12th July 2016) - Herrmann, Howard C.; Thourani, Vinod H.; Kodali, Susheel K.; Makkar, Raj R.; Szeto, Wilson Y.; Anwaruddin, Saif; Desai, Nimesh; Lim, Scott; Malaisrie, S. Chris; Kereiakes, Dean J.; Ramee, Steven; Greason, Kevin L.; et al.
Abstract : Background: In the initial PARTNER trial (Placement of Aortic Transcatheter Valves) of transcatheter aortic valve replacement for high-risk (HR) and inoperable patients, mortality at 1 year was 24% in HR and 31% in inoperable patients. A recent report of the 30-day outcomes with the low-profile SAPIEN 3 transcatheter aortic valve replacement system demonstrated very low rates of adverse events, but little is known about the longer-term outcomes with this device. Methods: Between October 2013 and September 2014, 583 HR (65%) or inoperable (35%) patients were treated via the transfemoral (84%) or transapical/transaortic (16%) access route at 29 US sites. Major clinical events at 1 year were adjudicated by an independent clinical events committee, and echocardiographic results were analyzed by a core laboratory. Results: Baseline characteristics included age of 83 years, 42% female, and median Society of Thoracic Surgeons score of 8.4%. At the 1-year follow-up, survival (all-cause) was 85.6% for all patients, 87.3% in the HR subgroup, and 82.3% in the inoperable subgroup. Survival free of all-cause and cardiovascular mortality in the transfemoral patients from the HR cohort was 87.7% and 93.3%, respectively. There was no severe paravalvular leak. Moderate paravalvular leak (2.7%) was associated with an increase in mortality at 1 year, whereas mild paravalvular leak had no significant association with mortality. Symptomatic improvement as assessed by the percentage of patients in New York Heart Association class III and IV (90.1% to 7.7% at 1 year; P <0.0001) and by Kansas City Cardiomyopathy Questionnaire overall summary score (improved from 46.9 to 72.4; P <0.0001) was marked. Multivariable predictors of 1-year mortality included alternative access, Society of Thoracic Surgeons score, and disabling stroke. Conclusions: In this large, adjudicated registry of SAPIEN 3 HR and inoperable patients, the very low rates of important complications resulted in a strikingly low mortality rate at 1 year. Between 30 and 365 days, the incidence of moderate paravalvular aortic regurgitation did not increase, and no association between mild paravalvular leak and 1-year mortality was observed, although a small increase in disabling stroke occurred. These results, which likely reflect device iteration and procedural evolution, support the use of transcatheter aortic valve replacement as the preferred therapy in HR and inoperable patients with aortic stenosis. Clinical Trial Registration: : URL:http://www.clinicaltrials.gov . Unique identifier: NCT01314313.